Freedom And Responsibility Of The Electronic Press In Algeria In According To The Media Law Of 2012 Comparative Analytical Study "algeria, Morocco And Tunisia - زعيطي امينة; برناوي راضية (International Journal of Social Communication, 2018)
ABSTRACT : The study deals with the legislative and regulatory framework for electronic media in the Arab Maghreb countries “Algeria, Tunisia and Morocco”, in a try to discuss the particularity of this digital press, which was able to impose itself in a short period of time as a source of information, especially that the electronic media has presented a new media reality and raised the traditional media to the level of sovereignty in terms of proliferation and managed to penetrate all the geographical and temporal barriers. The Maghreb countries, like other countries, have rushed to put in place a legal tool to regulate this modern media, which has gone beyond, if we could say, the obstacles of traditional media thanks to its characteristics. The researcher tackled the study on the basis of comparative analytical reference, including the legal approach, where we will try through our study to test the relationship between the concepts of freedom and responsibility in the Algerian electronic media environment in the light of the 2012 law of media, and compare between the laws of press and publication in the Maghreb countries, "Algeria, Morocco, Tunisia."